Writing a nation: essays in Malaysian literature - Quayum, Mohammad Abdul (IIUM Press, 2009)
This book provides a collection of essays on literature in three different languages in Malaysia: Malay, Chinese and English. There are essays that investigate Malay writers and works from the different periods, and several that examine writers and works in English. There is one essay that interrogates the “Mahua” literary critics. The themes explored in the chapters range from gender, ethnicity, religion, language and identity to nationalism and transnationalism. However, majority of the essays address, in one way or another, the issue of Malaysian nationalism and how Malaysia should form its national identity. With its inclusive approach, the book is likely to set a new direction in Malaysian literary criticism, and create a better sense of unity among the writers. Readers, as well as researchers, will find the book a rich source of information on Malaysian literature, history and culture.